Public listening – the Form of work of the National Assembly - Pajvančić, Marijana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The highlight of this enclosure is the institution of public listening. This is            a new form of work of the National Assembly of the Republic of Serbia, and one of the          forms of direct participation of citizens in the performance of public government. Public listening enables citizens to participate directly in the legislative procedure and decision making on laws and other acts which are adopted by the National Assembly